Relationship between periodontitis and subclinical risk indicators for chronic non-communicable diseases - Fernanda Cristina Figueira TEIXEIRA; Letícia MARIN-LEON; Everton Padilha GOMES; Alice Moreira Neves PEDRÃO; Alexandre da Costa PEREIRA; Priscila Maria Stolses Bergamo FRANCISCO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract In view of the epidemiological relevance of periodontal disease and chronic noncommunicable diseases, the study aimed to evaluate the relationship between them through subclinical indicators of systemic risk in a population group with healthy habits, including alcohol and tobacco abstinence. A complete periodontal examination of six sites per tooth was performed in a sample of 420 participants from the Advento study (Sao Paulo), submitted to anthropometric and laboratory evaluation. Periodontitis was defined and classified based on the Community Periodontal Index score 3 (periodontal pocket = 4-5 mm) and score 4 (periodontal pocket ≥ 6 mm). The prevalence of mild/moderate and severe periodontitis was 20% and 8.2%, respectively. Both categories of periodontal disease had significantly higher levels of triglycerides, C-reactive protein, calcium score, and calcium percentile, whereas blood glucose after tolerance test was significantly higher among people with severe periodontitis and HDL-c levels were lower (p < 0.05). Young adults with severe periodontitis had significantly higher prevalence of obesity, pre-diabetes, hypertension, and metabolic syndrome. Besides these conditions, the older adults with severe periodontitis had significantly higher prevalence of dyslipidemia and subclinical atherosclerosis. The group with periodontitis had also a higher coronary heart disease risk based on the PROCAM score (p < 0.05). The results indicated associations of periodontitis with several systemic indicators for chronic noncommunicable diseases, and highlighted the need for multiprofessional measures in the whole care of patients.